2010
DOI: 10.1136/hrt.2010.201889
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital triple antiplatelet therapy in patients with acute ST elevation myocardial infarction leads to better platelet aggregation inhibition and clinical outcome than dual antiplatelet therapy

Abstract: 60 min of prehospital initiated antiplatelet treatment including high-dose tirofiban resulted in higher levels of IPA compared to pretreatment with acetylsalicylic acid and high-dose clopidogrel alone, even after longer pretreatment times. Levels of IPA were significantly related to ST resolution and MACE, including stent thrombosis. This substudy confirms the main findings of the On-TIME2 trial that clopidogrel alone is suboptimal, even at high dose and administered well in advance of primary PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…Furthermore, several studies have suggested that patients exhibiting high on-treatment platelet reactivity to both aspirin and clopidogrel simultaneously are at an even higher risk of atherothrombotic events 15–18. This is of utmost importance, since several studies have suggested the benefit of tailoring therapy in these patients 9 19 20. The POPular study (The Do P latelet Function Assays Predict Clinical O utcomes in Clopidogrel Pretreated Patients Undergoing Elective P CI) demonstrated that aggregation-based tests were able to predict the occurrence of an adverse cardiovascular event in patients undergoing elective PCI with stent implantation 10.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies have suggested that patients exhibiting high on-treatment platelet reactivity to both aspirin and clopidogrel simultaneously are at an even higher risk of atherothrombotic events 15–18. This is of utmost importance, since several studies have suggested the benefit of tailoring therapy in these patients 9 19 20. The POPular study (The Do P latelet Function Assays Predict Clinical O utcomes in Clopidogrel Pretreated Patients Undergoing Elective P CI) demonstrated that aggregation-based tests were able to predict the occurrence of an adverse cardiovascular event in patients undergoing elective PCI with stent implantation 10.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, as our study showed a high overall level of coverage within a week after stent positioning, OCT assessment may be encouraged in the early phase (1–3 months) to decide whether to interrupt the treatment with dual antiplatelet treatment 22. However, further studies are needed to select the appropriate timing and the pattern of uncoverage of patients at risk of stent thrombosis.…”
Section: Discussionmentioning
confidence: 83%
“…The limitations of dual antiplatelet therapy with aspirin and clopidogrel have been further illustrated by the on-TIME-2 trial, in which patients undergoing primary PCI were randomised to additional prehospital tirofiban or placebo. 42 The addition of tirofiban produced more effective platelet inhibition than aspirin and clopidogrel alone, and this was associated with a reduction in MACE and early stent thrombosis. On-TIME-2 lends further support to guideline recommendations for early glycoprotein IIb/IIIa inhibition together with dual antiplatelet therapy in patients undergoing primary PCI.…”
Section: Antiplatelet Therapiesdwhat's New?mentioning
confidence: 99%